Eso Astrophysics Symposia
DOI: 10.1007/10856495_60
|View full text |Cite
|
Sign up to set email alerts
|

Why Do AGN Lighthouses Switch Off?

Abstract: Abstract. Nearby galactic nuclei are observed to be very much dimmer than active galactic nuclei in distant galaxies. The Chandra X-ray Observatory has provided a definitive explanation for why this is so. With its excellent angular resolution, Chandra has imaged hot X-ray-emitting gas close to the gravitational capture radius of a handful of supermassive black holes, including Sgr A * in the nucleus of our own Galaxy. These observations provide direct and reliable estimates of the Bondi mass accretion ratė M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 131 publications
(199 reference statements)
2
19
0
Order By: Relevance
“…We then tested the case of a non-zero value for R in and found that only disks with inner holes as large as 0.1 ∼ 10 16 cm ∼ 10 4 R g yield NIR "echoes" that are weak enough to escape the observational constraints. As such, our results are in complete agreement with the previous results by Falcke & Melia (1997) and Narayan (2002), who also ruled out the existence of an optically thick disk with R in = 0 in Sgr A * .…”
Section: Optically Thick Disksupporting
confidence: 93%
See 1 more Smart Citation
“…We then tested the case of a non-zero value for R in and found that only disks with inner holes as large as 0.1 ∼ 10 16 cm ∼ 10 4 R g yield NIR "echoes" that are weak enough to escape the observational constraints. As such, our results are in complete agreement with the previous results by Falcke & Melia (1997) and Narayan (2002), who also ruled out the existence of an optically thick disk with R in = 0 in Sgr A * .…”
Section: Optically Thick Disksupporting
confidence: 93%
“…In addition, the disk presence may help to explain (Nayakshin 2003;) two major mysteries of Sgr A * : its amazingly low luminosity (e.g., see Baganoff 2003, and reviews by Send offprint requests to: J. Cuadra, e-mail: jcuadra@MPA-Garching.MPG.DE Melia & Falcke 2001;Narayan 2002) and the recently discovered large amplitude X-ray flares (Baganoff et al 2001). Direct observational detection of the disk could be possible if the disk were massive and thus bright enough (e.g., Falcke & Melia 1997;Narayan 2002) but a very dim inactive disk could have eluded such detection . pointed out that the three dimensional orbits of stars such as S2 could be used to test the putative disk hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The nonthermal flux can be used to derive an upper limit to the disk luminosity, L disk 10 43 erg s −1 (Ferrarese & Ford 1999;Ho 2009), which in units of Eddington luminosity, L Edd , is L disk /L Edd 10 −4 for an estimated black hole mass M BH = 6 × 10 8 M (Ferrarese & Ford 1999). The sub-Eddington regime could indicate the presence of a radiatively inefficient disk (here we generically refer to the class of models as radiatively inefficient accretion flows, RIAFs, see Narayan 2002, for a review). Ghisellini & Celotti (2001) demonstrated that the FRI-FRII dividing line in the radio luminosity vs optical galaxy luminosity plane (proposed by Ledlow & Owen 1996) can be expressed in terms of a critical accretion rate of 10 −2 −10 −3 , in units of Eddington accretion, and suggested that this might reflect a change in the accretion mode from a standard optically thick geometrically thin efficient Shakura-Sunyaev disk (Shakura & Sunyaev 1973) to a RIAF.…”
Section: Jet Power Versus Accretionmentioning
confidence: 99%
“…At low accretion mass rates ofṀ Ṁ Edd , the radiative cooling of the disk becomes inefficient. These accretion flows are generally called radiatively inefficient accretion flows (RIAFs) (Narayan 2002). This class of disk flow also includes ADAFs.…”
Section: Introductionmentioning
confidence: 99%